Adcock: Liberalism and Political Science - Boncourt, Thibaud; Hauptmann, Emily; Berndtson, Erkki; Adcock, Robert (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
Introduction to the Symposium by Thibaud Boncourt The following contributions stem from a roundtable held in Poznan, Poland in July 2016 at the International Political Science Association’s Congress. The roundtable was put together by IPSA’s Research Committee 33, which focuses on the history of political science as a discipline. Contributors produced a stimulating debate on Robert Adcock’s award winning Liberalism and the Emergence of Political Science: A Transatlantic Tale. As its title suggests, this important book weaves two narratives together. First, it sheds a new light on the history of liberalism, by highlighting the way in which liberal political thought changed between the early 19th century and the early 20th century. Adcock highlights the transition from “democratised classical liberalism” to alternative conceptions of the liberal tradition such as “progressive liberalism” and “disenchanted classical liberalism”. Second, the book documents the history of the emergence of American political science. By studying the pioneers of this discipline, Adcock analyses the progressive spread and institutionalisation of political science in America until the landmark creation of the American Political Science Association (APSA, 1903). These two stories are interesting in themselves but what makes Adcock’s argument more so is that he weaves these two trends together. He shows convincingly how the development of one of the biggest political discourses and the institutionalisation of political science fuelled one another. By linking the history of the discipline to that of political power, Adcock’s impressive study resonates with other great work on the subject such as those of Sonja Amadae (2003) and Nicolas Guilhot (2005). Another of the book’s strengths lies in the choice of adopting a transatlantic perspective. In line with recent literature, Adcock goes beyond narratives of intellectual history as shaped by “national traditions” to emphasise the transnational exchanges that shape the history of political thought. Thus, Adcock first traces the history of liberalism in Europe, before analysing how it was imported in American academia. The book tells the story of the “Americanisation” of liberalism, understood as the way in which European liberal beliefs were adapted by American scholars to address American political and economic realities. In order to discuss several aspects of this stimulating, multi-layered book, the roundtable gathered specialists in the history of political thought, history of political science as a discipline, and the internationalisation of the social sciences. The following three contributions raise some of the topics that were discussed at the roundtable, as well as new ones. Robert Adcock’s rejoinder discusses these topics by expanding on the book’s argument.